As the exercise suggests, let's call the two consecutive integers [tex] x [/tex] and [/tex] x+2 [/tex]. In fact, if [tex] x [/tex] is even, the next number, [tex] x+1 [/tex] is odd, and the next number [tex] (x+1)+1=x+2 [/tex] is again even.
Moreover, since the two numbers are positive, the square of the bigger one is actually bigger, so the difference is [tex] (x+2)^2-x^2 [/tex]
In fact, note that if the numbers were negative, for example -6 and -4, their squares would be 36 and 16, so you should have subtracted
[tex] (-6)^2-(-4)^2 = 36-16 = 20 [/tex]
So, the difference of their squares is
[tex] (x+2)^2 - x^2 = (x^2+4x+4)-x^2 = 4x+4 [/tex]
And we know that this difference is 68, so the equation is
[tex] 4x+4=68 \iff 4x = 64 \iff x = \dfrac{64}{4} = 16 [/tex]
So, the two consecutive even integers are 16 and 18.
Let's check the answer!
The difference of their squares is
[tex] 18^2-16^2 = 324-256=68 [/tex]